FACTORS INFLUENCING THE USE OF E-FILING MODERATED WITH INFORMATION TECHNOLOGY MASTERY - Linda Santiso; Andreas Bambang Daryatno (International Journal of Application on Economics and Business, 2024)
The purpose of this study is to provide empirical evidence whether the influence of perception of use, perception of convenience, and security and confidentiality on the interest of individual taxpayers in using E-filing with mastery of information technology as a moderating variable. The data used in this study is primary data through a questionnaire in the form of google which is distributed to individual taxpayers who have filled out and reported online taxes in Jakarta. Data processing is using SmartPLS 3. The results of the study prove that before moderation, the variables perception of usefulness, convenience, security and confidentiality have a significant influence on the use of e_filling. Moderation is carried out so that the perceptual variables that are useful for, security and confidentiality still provide significant results, while the variables after turning become insignificant, Perceptions of the usefulness, progress, security, and confidentiality of individual taxpayers have no effect on the interest in using E-filing which is moderated by mastery of technology. information, this means that mastery of information technology is not able to moderate perceptions of usefulness, timeliness, security, and confidentiality.